Rezension von: Schuster, Felix (Hg.), Schwäbisches Heimatbuch 1938 - Senn, Ernst (Zollerheimat, 1939)
Schwäbisches Heimatbuch 1938, hg. von Felix Schuster, 1938. 224, 36 Seiten , [2] Blatt : zahlr. Ill., graph. Darst., Kt.